ANALISIS APLIKASI DETEKSI DINI STRES KERJA DENGAN METODE SYSTEM USABILITY SCALE (SUS) - Tri Suwarno; Feri Luvita Sari (Jurnal Sistem Informasi Galuh, 2026)
Work stress is a significant challenge that can affect the productivity and well-being of educational staff in higher education environments. This study aims to develop a web-based early detection application for work stress as a promotive and preventive mental health measure for the educational staff at the Faculty of Medicine, Universitas Islam Indonesia (FK UII). The research utilized the Waterfall model for system development. The stages included requirements analysis, system design, implementation, functional testing, and usability evaluation. The application was developed using the PHP programming language and integrates two psychometric scales that have been validated and adapted into Indonesian: the Role Stress Scale and the Job Stress Scale. System evaluation was conducted using a quantitative approach via the System Usability Scale (SUS) questionnaire, completed by 63 educational staff respondents. The testing results demonstrated a 100% functional success rate for key features such as registration, login, questionnaire completion, and result access, indicating that the application prototype functioned according to the technical plan. An average SUS score of 79.56 indicates that the application possesses an excellent level of usability, surpassing industry standards. This application is expected to serve as an innovative digital solution that supports the mental health of educational staff within higher education institution.